Automating Dietary Expertise: The Challenge of Making a Food-Tracking App for Everyone (Medicine Anthropology Theory, 2025)
Digitally tracking food and eating has become a widespread activity. Scholars in anthropology, sociology and science and technology studies have problematised the personal and social implications of dietary tracking and the metrification of food and eating. Metrification has contributed to the emergence of new types of relevant expertise and new experts of eating and health. This warrants in-depth research to better understand the forming, negotiation, establishment and effects of new expertise.Drawing on a sociomaterial perspective, this article explores these questions by reflecting on the development of an automated dietary tracking and intervention app. The article focuses on seeking feedback on mock-ups and prototypes of the app from potential users and non-users in ‘go-alongs’ and interviews, and in focus groups. The analysis revealed that the delegation of dietary expertise to an automated system poses a challenge for many participants. They emphasised what is neglected in the process—including their dietary but also bodily and sociocultural expertise. Our study contributes to an understanding of how dietary tracking and delegating expertise to an automated system appeals to users whose food values align with metrics used in the app but also users who accept to delegate specific forms of care to the technology.